Braving the Waves: Issues and Coping of College Teachers in the Online Pedagogy - Wilter C. Friales; Christian Jade D. Pama; Mark Jhon L. Umadhay; Cherryl Zane A. Labuaya; Kannah Mari G. Carreon; Desyree Divine D. Gregorio; Devi Ann E. Manansala (CV. Literasi Indonesia, 2022)
The global experiences of the pandemic situation have introduced an unnecessary shift in the teaching-learning process setup among the different departments, curriculum developers, teachers, instructors, professors, students, pupils, and parents to adjust to the emerging needs that an online class format requires. This research aims to describe the experiences of the College teachers of Notre Dame of Marbel University in the online pedagogy. This is descriptive qualitative research using the in-depth interview as a data gathering method. Thematic analysis was conducted to get the emerging themes based on the narratives and sharing of the participants. The challenges of the teachers in the technical aspects are unupdated devices, problems with the main sources of technology, unfamiliarity with applications, and technological gaps; their challenges are difficulty in social interaction, not being technologically inclined, dishonesty of students, time management; emotional challenges are pressure and fear, mental exhaustion, dishonesty, slow internet connection. The coping mechanisms of the language teachers involve keeping one’s circle close, doing things they love, social media, acceptance, practice, and collaborative learning. Along with these are the goals of the teachers for their students, which are honesty, knowledge, and to inspire.